Global Value Chains and Economic Upgrading in Developing Countries - Kore Marc Guei; Ireen Choga (Managing Global Transitions, 2022)
The emergence of global value chains (GVCS) has allowed countries to specialise in the production of specific inputs (intermediate goods and final goods), which has a direct implication for productivity. This paper explores the impact of GVCSon the economic upgrading of developing economies. Specifically, our analysis relates to the effect of foreign value added in gross exports (GVCS) on domestic value-added content of gross exports (economic upgrading), which includes the added value that emanates from all the industries of the exporting country to their trading partners. The sample covers 50 countries (22 developing and 28 advanced countries) over the period 2005–2015.We employ both a pooled ols and a system GMM method. We contribute to the literature by differentiating between trade flows from developing economies (South-South) and developed economies (South-North). The results indicate a positive effect between gvcs participation and economic upgrading, with the effect being stronger in the case of South-North integration. Further, the results support the view that infrastructure development can play a key role in supporting the economic development of developing economies. gdp per capita, innovation, and institutional quality can all promote economic upgrading even though their effects vary across trade flows.